Perkembangan Lembaga Pendidikan Islam Kontemporer - Arif Fiandi; Darul Ilmi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
The purpose of writing this article is to find out and discuss the development of contemporary Islamic educational institutions. This study uses the literature review method by gathering information from literary sources, such as books, articles, research reports, and other sources that are relevant to the topics discussed. Islamic educational institutions which at first took place in a simple manner with simple management as well. However, along with the times and the development of the world of education, Islamic educational institutions are also developing. The development of Islamic educational institutions is a necessity and must occur. The results of this study are that there are five periods in the development of Islamic educational institutions, namely: the coaching period, the golden period, the decline period, the stagnation period and the modern period. It is this modern period Islamic educational institution that has developed to date, which is called a contemporary Islamic educational institution. Contemporary Islamic educational institutions exist in the form of formal, non-formal and informal educational institutions. Contemporary Islamic educational institutions are managed with modern management, complete infrastructure, integrated curriculum, and can meet the expectations of society, especially formal contemporary Islamic educational institutions.